Communication of Central Bank Thinking and Inflation Dynamics - Tang, Man-Keung (IMF Working Papers; Working Paper ;, 2011)
This paper studies the role of central bank communication of its economic assessment in shaping inflation dynamics. Imperfect information about the central bank's assessment - or the basis for monetary policy decisions - could complicate the private sector's learning about its policy response function. We show how clear central bank communication, which facilitates agents' understanding of policy reasoning, could bring about less volatile inflation and interest rate dynamics, and afford the authorities with greater policy flexibility. We then estimate a simple monetary model to fit the Mexican economy, and use the suggested paramters to illustrate the model's quantitative implications in scenarios where the timing, nature and persistence of shocks are uncertain.